Environmental Effects and Morbidity Patterns Associated with the Activities of an Oil and Gas Installation in the Niger Delta, Nigeria - Kennedy A. Osakwe (Medical Science: Trends and Innovations Vol. 5, 2025)
Aim: The present study aimed to determine the perceived environmental effects and morbidity patterns associated with the activities of an oil and gas installation in the Niger Delta region of Nigeria. Background: There are several high-risk jobs in the oil sector worldwide, including seismic exploration, building, drilling, production, and maintenance. Exposure to generated dangers may affect workers. Workers in oil and gas installations are typically at risk of developing occupational illnesses due to exposure to related dangers and the intensity of their work. There have also apparently been reports linking these operations to environmental issues. There are several high-risk jobs in the oil sector worldwide, including seismic exploration, building, drilling, production, and maintenance. Exposure to generated dangers may affect workers. Workers in oil and gas installations are typically at risk of developing occupational illnesses due to exposure to related dangers and the intensity of their work. There have also apparently been reports linking these operations to environmental issues. Methods: A descriptive, cross-sectional study design was utilized in conducting this study between August 2019 and January 2020. The study group comprised engineers and technicians of various oil and gas specialities. A random sampling method was used to select 256 personnel from the study population. A self-administered questionnaire was administered to the personnel of the facility. Data was analysed using the Statistical Package for Scientific Solutions (SPSS) version 17.0 (statistical software package) for analyses. Ethical considerations were adhered to during this study. Results: Common complaints include transient tinnitus (97.3%), joint pain of varying degrees (83.6%), occasional prickling sensation in the skin (78.1%) and the lowest frequency of health effects was claims of stressful feeling (56.6%). Environmental problems including the destruction of aquatic biodiversity as well as water contamination were reported in this study. Several environmental challenges associated with petroleum exploration and production activities were reported to be observed by the study respondents. Some of these problems included the destruction of economic plantations, contamination of the river water as well as death of aquatic creatures. Conclusion: This study found the experience of several morbidities by the respondents. They also reported observation of certain environmental problems related to oil exploratory activities at the oil and gas installation. It is recommended that a regular review of measures be put in place to prevent these health and environmental problems from occurring in or around oil and gas installations located in Nigeria. Training and retraining of the workers on the need for adherence to health and safety precautions to prevent the occurrence of morbidities associated with their work should also be regularly done.